P40 Fast track jaundice clinic: the standard of care for hepatobiliary malignancy?. (6th September 2011) - Young, K; Dundas, P; Vijayan, B; Fraser, A
Abstract : Introduction: The Scottish Government has stated that 95% of people referred urgently with a suspicion of cancer should begin treatment within 62 days of receipt of referral.1 Dedicated fast track clinics with pre-booked appointments and scheduled investigations with rapid reporting can ensure urgent referrals are processed within appropriate timescales.2 Hepatobiliary malignancy often presents with jaundice and therefore The Fast Track Jaundice clinic was established in NHS Grampian in June 2006.3 Its aim was to provide rapid diagnosis of jaundiced patients enabling early management or treatment. This protocol driven clinic is run by the Hepatology Nurse Specialist with medical support. Referrals are faxed and patients who meet the criteria for the clinic are contacted by telephone and given an appointment date and time within a week of referral. The clinic operates weekly with three reserved appointment slots for ultrasound and two for CT scan. Endoscopic Retrograde Cholangiopancreatography (ERCP) is available three times per week. Aim: The aims of this study were: To describe the demographics and diagnoses of patients referred with jaundice. To assess the time from referral to treatment in patients presenting with malignancy. Method: The information was obtained from the NHS Grampian Fast Track Jaundice clinic Microsoft Access database and the hospital Patient Management System (PMS). The Scottish Care Information (SCI) store and hospital LABS system were accessed to obtain dates of investigations and results. Results: In total there were 172 referrals and all but one attended. The majority, 150 (87%) were referred by their GP, the remainder came from a variety of sources. The number of referrals has increased each year. The mean age at date of clinic appointment was 63 years (range 18–94, SD 16.7) and 116 (67%) were male. The median number of days from referral to clinic appointment was 5 (range 0–20, IQR 2). The reasons that patients waited longer than expected for a clinic appointment included: patient choice, inability to contact the patient and lack of capacity at next clinic. The aetiology of jaundice was: gallstones 65 (38%), malignancy 50 (29%), alcohol hepatitis 19 (11%), or an alternative diagnosis in 37 (22%). A CT scan was required for diagnostic or staging purposes in 90 (53%) with 74 (82%) of CT scans performed on the same day as the clinic. The CT scan had been performed prior to the clinic in 2 (2%) with the remaining scans occurring sometime following clinic. Of the 50 patients with a malignancy, 13 (26%) had surgery with only 2 operations being outwith the 62-day timeframe (median time from clinic 36 days (range 4–99, IQR 38)). Of the remaining 37 (74%) who did not have surgery, 23 (62%) had ERCP (median time from clinic 3 days (range 1–38, IQR 7)) and 6 (16%) had PTC (mean time from clinic 9 days (range 4–16, SD 4.32)). The remaining 8 (22%) presented with such advanced disease that only palliative care was offered. Of those with malignancy 33/50 (66%) have died with a median time from clinic to death of 127 days (range 5–781 IQR 344). Conclusion: The introduction of The Fast Track Jaundice Clinic has resulted in patients with malignancy having clinical review and investigations performed rapidly with >95% receiving definitive treatment within 62 days of referral. The recognition of this service in providing timely, appropriate care has resulted in a steady increase in the number of referrals. We suggest that this model of service delivery should be considered as the standard of care for patients with suspected hepatobiliary malignancy presenting with jaundice.